Strategi Penipuan pada Teks Fake News Berbahasa Prancis Terkait Emmanuel Macron di Media Sosial - Annisa Fitriani Kalsum; Merry Andriani (Sasdaya: Gadjah Mada Journal of Humanities, 2022)
Social media has made it easier for people to access information, especially related to viral news. However, this convenience has not only had a positive impact but has provided space for the transmission of false information (fake news). This study examines how the characteristics of fake news texts are to trick social media users into false information. The object of the research is in the form of fake news text in French related to Emmanuel Macron which has been verified as fake news by the fact-checking platform. Through qualitative descriptive methods and Fairclough textual analysis, five fake news text fraud strategies were found, namely (1) loading provocative invitations, (2) manipulating data through images, (3) manipulating information through grammar, (4) manipulating facts through media sources, (5) includes clickbait and provocative titles. Furthermore, Emmanuel Macron in the fake news text is represented as a leader who has a negative image with the aim of provoking the public.